(untitled) (Journal of Educational Sciences, 2016)
The purpose of the article the definition of the role of training materials in maintaining motivation in studying a foreign language in school. To address the problem of motivation training, you can go different ways. This article touches upon the issues connected with the role of training materials in maintaining motivation in studying a foreign language in school. The question of maintaining motivation is relevant because, in General opinion, the vast majority of students learning a foreign language with enthusiasm and a desire to succeed. This fact is a strong emotional charge, laying a strong motivation and a positive attitude towards a foreign language as an academic discipline. But such an attitude to the ultimate goal of training is not enough to guarantee success, if students during the studies is not createdemotionally positive attitude to the process of learning English language into the regular practice of this subject. One of the forms of motivation, satisfaction is received by students successfully mastering by knowledge, skills and competencies. Educational effectiveness of the principle of significance is determined by a number of objective and subjective reasons, which include: the authority of the master, system of promising lines of practical application of the obtained knowledge, the presence of the target on the lesson and understanding of its significance. One of the main factors promoting the principle significance of the acquired knowledge and interest in the study of foreign language in high school is, apparently, the identity and authority of the master, his ability to interesting teach the subject.